الوضع تحت المراقبة الإلكــترونية في قانون تنظيم السجون وإعادة الإدماج الاجتماعي للمحبوسين - خطاب كريمة (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2023)
في إطار تخطي عدد من الصعوبات التي تعرفها منظومة العقوبات خاصة ما تعلّق منها بمشكل الاكتظاظ في المؤسسات العقابية، أدركت التشريعات الجزائية الحديثة أن نظام العقوبات الذي يعتمد أساسا على العقوبة السالبة للحرية في حاجة ماسة إلى مراجعة، ودون المساس بالمبادئ العامة للقانون الجنائي عملت العديد من الدول على تطوير أنظمتها العقابية بتبنيها لأساليب جديدة لتنفيذ عقوبة الحبس، على أن تضمن هذه الأخيرة تحقيق الردع من خلال الإصلاح وإعادة التأهيل وبالنتيجة تفادي العودة لتكرار الجريمة، وعليه تصب دراستنا على إجراء إحالة المحكوم عليه لقضاء عقوبته في المنزل تحت مراقبة الكترونية، وهو أسلوب لتنفيذ العقوبة السالبة للحرية لا سيما قصيرة المدة خارج المؤسسة العقابية، وقد تبنى المشرع الجزائري هذا الأسلوب لمراقبة المحكوم عليه عن بعد في إطار إصلاح قطاع العدالة. Abstract: In the context of overcoming a number of difficulties facing the penal system, especially those related to the problem of overcrowding in penal institutions, modern punitive legislations realized that the penal system based mainly on freedom-depriving punishment and its implementation, is in dire need of revision. Without sacrificing the general principles of law, many countries have worked to develop their penal systems by adopting new methods to implement the prison sentence, provided that the latter ensures the achievement of deterrence through reform and rehabilitation resulting in avoiding the repetition of the crime. Accordingly, our study focuses on the procedure of serving the sentence at the home under electronic surveillance, it is a method of executing freedom-depriving punishment, especially of a short period, outside the penal institution, and the Algerian legislator adopted this method to make surveillance over the convict from distance as a part of reforming the justice field.